Mycoflora Associated with the Seeds of Leucaena leucocephala - Sahu, R. K.; Agarwal, V. K. (Indian Forester, 2004)
A total of fourteen fungi have been detected by blotter and agar plate methods from the surface sterilized seeds of Lead tree (Leucaena leucocephala). These fungi were Alternaria alternata , A. tenuissima , Apispora montagnei , Arthrinium euphorbiae , Aspergillus flavus , A fumigatus , A. niger , Curvularia clavata , C. lunata , Fusarium sp. , F. pallidoroseum (syn. F. semitectum) , Paecilomyces variotii , Penicillium chrysogenum and Phoma sp. All fungi , except A. flavus , A. fumigatus , A. niger , C. lunata and Phoma sp. constitute new host records. Whereas , all except A. niger and F. pallidoroseum , have been reported for the first time from India , hence constitute new records on this host from India as well. Agar plate method was found superior over blotter method for the detection of seed borne fungi.